Pan-Africanism and African Citizenship: The Way Forward (Tamaddun, 2022)
This paper critically analyses Pan-Africanism as an ideology for the liberation of Africa, with a view to assessing the possibilities of a common African citizenship. This paper argues the claim that the focus of Pan-Africanism should shift from activism, agitations, and struggles to a univocal platform that will define authentic African identities by crystallising a common nationality for Africans on the continent and those in the diaspora. This claim is known to be rooted in the age-long African values of brotherhood, complementarity, and family hood (Ujamaa) that make Africans see other Africans as brothers who share the same humanity. This is different from the Africans of today who have assimilated western values of individualism, which are divisive and exclusive in nature, which in reality is a negation of authentic African personhood and society. This has given rise to ethnic agitations, xenophobic attacks, populism and hatred against "outsiders". Therefore, it is in the forging of common identities for Africans that African citizenship can be made possible. It should be the way forward for Pan-Africanism in the 21st century. Thus, in this paper, we employ the philosophical method of critical analysis in carrying out our investigation of the various issues that necessitated this research work.